Comparación de la eficiencia entre los sistemas de generación fotovoltáicos conectados a la red y los sistemas aislados - Salazar Díaz, Gabriel Alejandro (2014)
With the growing interest in protecting the environment by using renewable energy as alternative to the power generation and its application in the concept of distributed generation, this paper aims to calculate quickly and easily the efficiency by calculating the power and energy generation at each PV system connected to both the network and alone systems, then compare and determine which PV system has lower electrical losses and thus more efficient generation. It also took into account the economic portion of its cost-benefit represents investment in the short or long term in such generation systems. For this undertaken has used mathematical models applied in each of the components of photovoltaic systems and through calculation tools such as Matlab and Simulink platform for the respective simulations, it has been a great help as it relates to demonstrations along with the Solar Radiation hourly data values that have been provided by the Ministry of Environment on its website today and is free for all who need this information in future research.